Editors' Choice—Reaction Kinetics of Metal Deposition via Surface Limited Redox Replacement of Underpotentially Deposited Monolayer Studied by Surface Reflectivity and Open Circuit Potential Measurements. Issue 4 (28th January 2017) - Bulut, Ela; Wu, Dongjun; Dole, Nikhil; Kilic, Hasan; Brankovic, Stanko R.
Abstract : Presented work studies the relation between kinetics of metal deposition via surface limited redox replacement (SLRR) of underpotentially deposited (UPD) monolayer (ML) and experimental parameters of reaction solution such as meal ions concentrations and supporting electrolyte concentration. The model system is Au deposition on Au(111) via SLRR of Pb UPD ML. The rate constant of the SLRR reaction for different solution designs is determined from temporal change of electrode surface reflectivity and from the open circuit potential transients' analysis. The obtained results show clearly that reaction kinetics of metal deposition via SLRR of UPD ML is significantly affected by the design of the reaction solution i.e. the UPD metal ion, depositing metal ion, and supporting electrolyte concentrations. The ten-fold change of concentration of either solution parameter produces approximately the same change in the value of the rate constants. The presented results have fundamental importance for the future development and application of the metal deposition via SLRR of UPD ML. They offer a link between the reaction solution design and expected trend in SLRR reaction rate, which transposes to successful control of deposition flux, nucleation density and resulting morphology of the deposit.